Thermodynamics and selectivity of separation based on activity coefficients at infinite dilution of various solutes in ionic liquid [HMMIM][BF4]. (October 2018) - He, Zhuang-Zhuang; Zhai, Jia-Yu; Mu, Han; Zhang, Miao; Yu, Ying; Zheng, Jia-Li; Jiao, Yu-Hai; Ge, Ming-Lan; Wu, Rui-Xiang
Highlights: Measurements of activity coefficients at infinite dilution using GLC. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [HMMIM][BF4 ] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The linear free energy relationship (LFER) analysis of the results was performed. Graphical abstract: Abstract: The activity coefficients at infinite dilution ( γ i ∞ ), gas–liquid partition coefficients ( K L ) of organic solutes ( n -alkanes, alkenes, alkyl benzenes, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, chloromethanes, alcohols and 1, 4-dioxane) in the ionic liquid 1-Hexyl-2, 3-dimethylimidazolium tetrafluoroborate ([HMMIM][BF4 ]) have been measured using the gas–liquid chromatographic method (GLC) at five temperatures: 313.15 K, 323.15 K, 333.15 K, 343.15 K, 353.15 K. The density of [HMMIM][BF4 ], as a function of temperature, was determined in atmosphere. The values of the partial molar excess enthalpies at infinite dilution ( H ‾ i E, ∞ ) were derived from the temperature dependence of the In γ i ∞ values. The entropies ( T ref S ‾ i E, ∞ ) and Gibbs energies ( G ‾ i E, ∞ ) of organic solutes in [HMMIM][BF4 ] at a reference temperature T r ef = 298.15 K were calculated from the γ i ∞ values. The Hildebrand's solubility parameters of the IL [HMMIM][BF4 ] were determined by the regular solution theory (RST) combined with Flory ''combinatorial'' equation. Selectivity ( S ij ∞ ) and capacity ( k j ∞ ) at infinite dilution at 323.15 K have been determined for n -hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The results were analyzed in comparison to literature data for alkylimidazolium ionic liquids (ILs) with [ BF 4 ] - . The interaction between the IL and the individual solutes can be disclosed by the linear free energy relationship (LFER) analysis.